Extraintestinal Salmonellosis in the Immunocompromised: An Unusual Case of Pyomyositis - Veeraraghavan Meyyur Aravamudan; Phang Kee Fong; Pavel Singh; Jong Sze Chin; Yang Shiyao Sam; P. A. Tambyah (Case Reports in Medicine)
Salmonella infection can cause a wide range of presentations, predominantly gastrointestinal but occasionally with cardiovascular or other extraintestinal manifestations. The diagnosis of extraintestinal salmonellosis requires a high degree of clinical suspicion and should be considered in patients with deep-seated abscesses especially if they are immunocompromised. We present a case of salmonella causing gastroenteritis complicated by an intramuscular abscess of the left leg. With prompt recognition and multidisciplinary management, the patient recovered with no serious sequela.